The effect of support on Pd1Nb1 electrocatalysts for ethanol fuel cells. (May 2020) - Souza, Felipe M.; Nandenha, Julio; Oliveira, Vitor H.A.; Paz, Edson C.; Pinheiro, Victor S.; Aveiro, Luci R.; Parreira, Luanna S.; Silva, Júlio C.M.; Batista, Bruno L.; Neto, Almir O.; Santos, Mauro C.
Abstract: Pd1 Nb1 /C on different kinds of carbon black were prepared by a modified sol-gel method. The alkaline direct ethanol fuel cell (ADEFC) performance was performed first with the Pd1 Nb1 electrocatalysts and then by varying the fuel concentration. In CV, Pd1 Nb1 /Printex 6L (50:50 wt%) exhibited 2.2 times higher mass activity than that of the Pd/C (Alfa Aesar); their mass activities were 1300 and 590 mA mg Pd − 1, respectively. The best performance for the ADEFC was obtained using Pd1 Nb1 /Printex 6L, which yielded a maximum power density and cell voltage of 28 mW cm −2 and 1.17 V, respectively. The Pd1 Nb1 /Printex 6L electrocatalyst exhibited a more negative onset potential for the CO stripping reaction. We suggest that the higher hydrophilicity (contact angle) and higher degree of disorder of Printex 6L (Raman) corroborates these results. In addition, both bifunctional and electronic effects operated on the electrocatalyst due to the presence of metal oxides and alloys of PdNb (XRD), respectively, in the synthesized electrocatalysts. Therefore, it was notable that the support has an essential role—as important as the cocatalyst—in the electrocatalytic performance. Highlights: ● Pd1Nb1/C binary electrocatalysts supported on different carbon black to ADEFC. ● Pd1Nb1/Printex 6L exhibited 2.2 times higher activity compared to Pd/C (Alfa Aesar©). ● The best performance for the ADEFC was obtained using Pd1Nb1/Printex 6L. ● This performance indicates an excellent energy efficiency of approximately 92%. ● The Printex 6L showed here as the best support than other carbon blacks.